A experiência da construção do sujeito ético-político nos espaços do Fórum Bem Maior - Leite, Lidiane (2009)
This disquisition discusses the experience of construction of the ethical-political subject within a community development forum, called Bem Maior, located in the city of Vitória - ES. Based on a few experiences lived in Fórum Bem Maior and on the interviews with 16 active leaderships of this environment, this work looks forward to monitor the process of ethical-political constitution of subjectivity engendered at the point of the encounter with otherness. Mainly, reviews Michael Foucault's thoughts, using a few of his key concepts as theoretical tools in order to discuss the idea of citizenship and the relationship between ethics and politics. This discussion provided thought on the political experience located in the articulated plot between power and resistance, taken in accordance with the ethical care of themselves. This study was intended highlight the ethical component of the subjectivity constitution as indispensable to the construction of the political subject as citizen and the possibility of limiting relations of domination and subjection by an ethical exercise of care and cultivation of freedom.